2020
DOI: 10.1097/md.0000000000019685
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term intensive insulin therapy on α-cell function in patients with newly diagnosed type 2 diabetes

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…[6] Shortterm intensive insulin therapy can improve the pathophysiological defects underlying T2DM (insulin resistance, pancreatic β-cell dysfunction, and α-cell dysfunction). [5,7] Taylor et al [8] have shown that T2DM is a condition mainly caused by excessive, yet reversible, fat accumulation in the liver and pancreas, and reversal of T2DM requires a reduction in fat content in the liver and pancreas. The Diabetes Remission Clinical Trial (DiRECT) demonstrated that the ability of β cells in recovering their long-term function persists after diagnosis, changing the previous paradigm of irreversible loss of β-cell function in T2DM.…”
mentioning
confidence: 99%
“…[6] Shortterm intensive insulin therapy can improve the pathophysiological defects underlying T2DM (insulin resistance, pancreatic β-cell dysfunction, and α-cell dysfunction). [5,7] Taylor et al [8] have shown that T2DM is a condition mainly caused by excessive, yet reversible, fat accumulation in the liver and pancreas, and reversal of T2DM requires a reduction in fat content in the liver and pancreas. The Diabetes Remission Clinical Trial (DiRECT) demonstrated that the ability of β cells in recovering their long-term function persists after diagnosis, changing the previous paradigm of irreversible loss of β-cell function in T2DM.…”
mentioning
confidence: 99%